2022
DOI: 10.7717/peerj.12964
|View full text |Cite
|
Sign up to set email alerts
|

Climate in Africa sequentially shapes spring passage of Willow WarblerPhylloscopus trochilusacross the Baltic coast

Abstract: Background Many migrant birds have been returning to Europe earlier in spring since the 1980s. This has been attributed mostly to an earlier onset of spring in Europe, but we found the timing of Willow Warblers’ passage to be influenced by climate indices for Africa as much as those for Europe. Willow Warblers’ spring passage through northern Europe involves populations from different wintering quarters in Africa. We therefore expected that migration timing in the early, middle and late periods of spring would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 90 publications
(215 reference statements)
0
15
0
Order By: Relevance
“…Negative and positive values of AA indicated, respectively, earlier and later passage of spring than the long-term average curve for the species in focus. We then used the annual anomalies (AA) for each species' spring migration as the response variable in multiple regression models, with 15 climate indices and calendar year as explanatory variables; we used the same variables as in [23]. These were based on groups of months pertinent to the birds' life-stages during the year preceding the spring migration (Figure 3); see [23] and Sections 2.4 and 2.5 for details.…”
Section: Calculating the Annual Anomaly Of Spring Migration At Bukowo...mentioning
confidence: 99%
See 4 more Smart Citations
“…Negative and positive values of AA indicated, respectively, earlier and later passage of spring than the long-term average curve for the species in focus. We then used the annual anomalies (AA) for each species' spring migration as the response variable in multiple regression models, with 15 climate indices and calendar year as explanatory variables; we used the same variables as in [23]. These were based on groups of months pertinent to the birds' life-stages during the year preceding the spring migration (Figure 3); see [23] and Sections 2.4 and 2.5 for details.…”
Section: Calculating the Annual Anomaly Of Spring Migration At Bukowo...mentioning
confidence: 99%
“…We have shown that, in one long-distance migrant, the Willow Warbler, the combined effect of multiple indices of climate at both its breeding grounds in Europe and its nonbreeding grounds in western, eastern, and southern Africa explained not only the long-term trend to earlier arrival, but also nearly 60% of the year-to-year variation in timing of this species' spring migration in 1982-2017 at the Polish coast of the Baltic Sea [22,23]. Thus, we also expect that, in other long-distance migrants, a combination of several large-scale and local climate indices should help explain their spring arrival timing in Europe.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations